2022
DOI: 10.1088/1755-1315/951/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea coating by chitosan on the dynamics of ammonia concentration and rumen fermentation in vitro

Abstract: The aim of this study was to determine the effect of coating urea by chitosan at graded levels on ammonia concentration and rumen fermentation in vitro. This study used Factorial Randomized Complete Block Design (RCBD) to test ammonia parameter and Randomized Complete Block Design (RCBD) for pH, microbial protein synthesis, dry matter and organic matter digestibility, and Volatile Fatty Acid (VFA). The treatments tested were: P0 = addition non coating urea 1%; P1 = coating urea by chitosan 1%; P2 = coating ure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This may be because the ration contains an energy source. Similar findings were reported by De Queiroz Vieira et al [38] and Nayohan et al [34]. The pH level in the rumen is crucial for optimizing performance and stability by influencing the microbial population, rumen fermentation products, and regular physiological activity [32].…”
Section: In Vitro Fermentation Characteristics Of Sru Supplementation...supporting
confidence: 78%
See 3 more Smart Citations
“…This may be because the ration contains an energy source. Similar findings were reported by De Queiroz Vieira et al [38] and Nayohan et al [34]. The pH level in the rumen is crucial for optimizing performance and stability by influencing the microbial population, rumen fermentation products, and regular physiological activity [32].…”
Section: In Vitro Fermentation Characteristics Of Sru Supplementation...supporting
confidence: 78%
“…Because these two substances are closely related, particularly for single SRU and urea samples, NUE and ammonia evaporation from urea are enhanced by the chitosan contained in SRU [ 26 ]. Urea degradation in the rumen can be minimized by coating the material with a chitosan-based biopolymer [ 34 ]. In addition, gamma irradiation improves chitosan effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may occur because the rate of solubilization dependent of the material and method used to coat this urea. For example, a study 5 found that coating of urea chitosan did not bring significant effect on pH, dry matter and organic matter digestibility, microbial protein synthesis, and amonia concentration in the rumen. On the other hand, some authors 6 cite that the extrusion of urea with corn, in addition to controlling the release of nitrogen, improves the use of urea due to a better synchronization during the degradation of these ingredients.…”
Section: Introductionmentioning
confidence: 99%